Analisys of hot deformation behavior of super duplex stainless steel UNS S32760 through processing maps - Dias,Clayton Pereira (2016)
Abstract The need for materials with higher strength and corrosion resistance in corrosive environments, such as in the oil extraction in saline media, has led to the use of super duplex stainless steels in projects such as the Pre-sal. The manufacture of these materials involves the step of thermomechanical processing, whose performance depends on the workability of the material. Processing conditions in which the super duplex stainless steel UNS S32760 can be worked safely and in which the material can fail were investigated in this presentation. The physical simulation was performed by means of hot torsion testing. The tests were performed at temperatures ranging from 900°C to 1200°C and strain rates of 0.01s-1 to 10s-1. The evolution of strain rate sensitivity of flow stress (m) for deformation of 0.5 at all temperatures investigated here was determined. After attaining the values of m for each deformation condition, the values of the power dissipation efficiency (η) were calculated, an instability criterion (ξ) was applied, and processing maps were constructed. Using these maps, the effects of deformation conditions on the power dissipation efficiency and the material plastic instability were discussed. The domains of processing maps, the observed microstructures and the shape of plastic flow stress curves were associated.